Analisis Konten Media Sosial Instagram dalam Meningkatkan Engagement pada Akun Cinemagenda (@Linikini_Id) - Nugrani, Syabita Salma; Pranata, Rici Tri Harpin; Cholagi, Fahmi Fuad (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The rise of social media has transformed patterns of interaction and established a virtual public space for sharing information, influencing, and inspiring audiences. Content plays a crucial role as a medium of message delivery through a combination of visual elements and narrative to encourage interaction. This study aims to analyze the content of the Instagram account Cinemagenda (@linikini_id) and identify the most effective content category for increasing engagement. A qualitative content analysis method was applied to 20 Instagram feed posts published between April 10 and May 16, 2025. The content was classified into five categories: film recommendations, interesting facts, collaborations, interactive quizzes, and entertainment. The findings indicate that entertainment content is the most effective in maintaining and increasing organic engagement, driven by engaging visuals, relevant themes, and a communicative approach. Interactive quizzes can generate an instant spike in engagement but require limited scheduling due to resource constraints. Based on Milhinhos’ effectiveness indicators, content success is influenced by relevance, informative value, accuracy, ease of understanding, discoverability, visual consistency, and communicative language. These findings serve as a reference for designing more targeted and effective content strategies on social media.